Analysis of the Quality of Scientific Literacy Question Items on Biodiversity Material Using the ANATES Application - Fauziah Hervi; Syamsurizal Syamsurizal; Fitri Arsih; Linda Advinda; Mutia Sari (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to analyze the quality of scientific literacy questions on biodiversity material using the ANATES application. ANATES (Test Analysis) is a computer application specifically developed to measure and evaluate the quality of exam questions. The research was conducted by collecting data from a collection of scientific literacy questions on biodiversity material and then analyzing it using ANATES. This type of research is descriptive quantitative. This research was carried out at Padang State University. The research subjects are Biology students in 2023 who are taking basic science courses. The population is all biology students in 2023 who are taking basic science courses. In this case, the sample used was only one class, namely biology education class C, totaling 35 people. The instrument used was scientific literacy questions on biodiversity material, totaling 25 questions. Next, the items are analyzed using ANATES to evaluate validity, reliability, level of difficulty, discriminating power, and distractor quality. The results of the analysis provide an in-depth picture of the quality of the scientific literacy questions on biodiversity material. It is hoped that the findings of this research can contribute to the development of better evaluation instruments for measuring students' understanding of biodiversity material. The implications of this research can be used by teachers, curriculum developers, and educational researchers to improve the quality of science learning at the secondary education level